Towards Building New Partnership with Southeast Asia: Japan’s Initiatives and the Challenges Ahead - Mie OBA (East Asian Policy)
Beyond the 50th anniversary of ASEAN–Japan relations, their partnership is entering a new phase. Japan actively strives to promote regional order under the Free and Open Indo-Pacific (FOIP) banner to address challenges, such as the escalation of great power rivalry, the increasingly complicated strategic environment due to the Russia–Ukraine war and the Gaza crisis, and the emergence of the “Global South”. For Japan, strengthening its partnerships with Southeast Asia is becoming increasingly critical.